Insights into a hotspot in the Brasiliensis subcomplex (Hemiptera, Triatominae) by analysis of D2 domain of the nuclear gene 28S - Guerra, A. L. [UNESP]; Alevi, K. C. C. [UNESP]; Banho, C. A. [UNESP]; Oliveira, J. [UNESP]; Rosa, J. A. [UNESP]; Azeredo-Oliveira, M. T. V. [UNESP] (Funpec-editora, 2016)
The Brasiliensis subcomplex is a monophyletic group formed by the species Triatoma brasiliensis brasiliensis, T. b. macromelasoma, T. juazeirensis, T. melanica, and T. sherlocki. However, using cytogenetic data and experimental hybrid crosses, T. lenti and T. petrochiae were also grouped into this subcomplex. This study aims to analyze the properties of hotspot in the D2 domain of the nuclear gene 28S in all species of the Brasiliensis subcomplex as well as T. lenti and T. petrochiae. These species show two transversions at position 385 (G <-> C and T <-> G). We suggest that this mutation in haplotype 4 may be an initial molecular tool that supports the relationship of these species with the subcomplex. In addition to the transversion at haplotype 4, these species, aside from T. melanica, also possess a transversion at position 385 (G <-> T) in haplotype 1. Thus, we describe the hotspot mutations of the D2 domain of the nuclear gene 28S for species in Brasiliensis subcomplex as follows: three transversions are present at position 385 of haplotypes 1 and 4, which are shared by members of the subcomplex as well as T. lenti and T. petrochiae. These transversions may be considered a synapomorphy between these species. However, we emphasize that new phylogenetic studies should be conducted to evaluate whether T. lenti and T. petrochiae are truly members of the Brasiliensis subcomplex.
Keywords: Triatoma lenti; Triatoma petrochiae; Hotspot